2012
DOI: 10.5641/027013612800745059
|View full text |Cite
|
Sign up to set email alerts
|

Expert Anticipatory Skill in Striking Sports: A Review and a Model

Abstract: Expert performers in striking sports can hit objects moving at high speed with incredible precision. Exceptionally well developed anticipation skills are necessary to cope with the severe constraints on interception. In this papr we provide a review of the empirical evidence regarding expert interception in striking sports and propose a preliminary model of expert anticipation. Central to the review and the model is the notion that the visual information used to guide the sequential phases of the striking acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
135
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(143 citation statements)
references
References 0 publications
5
135
3
Order By: Relevance
“…This is an extremely robust finding within expertise research, as higher skill levels constantly give rise to superior anticipatory responses and thereby performance (Mann, Williams, Ward, & Janelle, 2007). Skilled performers possess greater perceptual-cognitive expertise when compared to their less-skilled counterparts, leading to a greater ability in making use of postural cue and situation specific probabilistic information (Müller & Abernethy, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This is an extremely robust finding within expertise research, as higher skill levels constantly give rise to superior anticipatory responses and thereby performance (Mann, Williams, Ward, & Janelle, 2007). Skilled performers possess greater perceptual-cognitive expertise when compared to their less-skilled counterparts, leading to a greater ability in making use of postural cue and situation specific probabilistic information (Müller & Abernethy, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…For example, expert performers within fast ball sports are able to decipher important cues from the probabilistic information available before the onset of any postural movements (Müller & Abernethy, 2012). In addition, Farrow and Reid (2012) found that older, more highly-skilled tennis performers were more able to utilise game score information to produce faster responses to serves within a simulated match situation than were younger, less-skilled players.…”
Section: Anxiety Anticipation and Contextmentioning
confidence: 97%
See 2 more Smart Citations
“…There may be a number of critical non-modifiable differences in task and environmental constraints between AVG and the real world. For example, previous research has highlighted that perceptions and timing of ball movement (bounce and spin) and opposition player movements are critical in ball sports (Abernethy, 1993;Muller & Abernethy, 2012). Therefore, the considerable differences in the displayed view of the opposition player and ball (i.e three dimensional real world players with physical ball strike versus two dimensional avatar and a ball that remains within a screen several meters from the player's 'bat') are certainly constraint differences that may impact on performance.…”
Section: Discussionmentioning
confidence: 99%